Bias Gender Dalam Pembelajaran Pendidikan Agama (Peran Perempuan Dalam Pendidikan Islam) - Ahmad Khori (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Stroke of the pen is intended for the generation of people, especially women who always persistent, in various fields. Differences are naturally clear, but on the other hand is still eager to help and take the opportunity to earn the coffers rupiah in helping the economy of the family in order to realize a coveted palace in the family. As a real step actualization of the first performance, always tawakal alallah; secondly, to uphold the dignity of women; third, keep the commitment to make changes toward better for the sake of the nation and the State; fourth, continuous learning dilakukana from informal to formal environment that gave birth to the character generation.